Are the pension systems sustainable? Comparative perspective of Slovakia pension reform - Botek, Ondrej (Magyar Gerontológia, 2024)
2004 Pension reform in Slovakia introduced important changes in the Slovak pension system. Previous pay-as-you-go system was replaced by an obligatory two pillar system, including pay-as-you-go and individual capitalisation pillars, supplemented by a voluntary third pillar of individual savings, organised by private companies.